Analysis of Successful Versus Failed Radiographic Outcomes After Cervical Deformity Surgery. Issue 13 (1st July 2018) - Protopsaltis, Themistocles S.; Ramchandran, Subaraman; Hamilton, D. Kojo; Sciubba, Daniel; Passias, Peter G.; Lafage, Virginie; Lafage, Renaud; Smith, Justin S.; Hart, Robert A.; Gupta, Munish; Burton, Douglas; Bess, Shay; et al.
Abstract : Study Design: Prospective multicenter cohort study with consecutive enrollment. Objective: To evaluate preoperative alignment and surgical factors associated with suboptimal early postoperative radiographic outcomes after surgery for cervical deformity. Summary of Background Data: Recent studies have demonstrated correlation between cervical sagittal alignment and patient-reported outcomes. Few studies have explored cervical deformity correction prospectively, and the factors that result in successful versus failed cervical alignment corrections remain unclear. Methods: Patients with adult cervical deformity (ACD) included with either cervical kyphosis more than 10°, C2-C7 sagittal vertical axis (cSVA) of more than 4 cm, or chin-brow vertical angle of more than 25°. Patients were categorized into failed outcomes group if cSVA of more than 4 cm or T1 slope and cervical lordosis (TS-CL) of more than 20° at 6 months postoperatively. Results: A total of 71 patients with ACD (mean age 62 yr, 56% women, 41% revisions) were included. Fourty-five had primary cervical deformities and 26 at the cervico-thoracic junction. Thirty-three (46.4%) had failed radiographic outcomes by cSVA and 46 (64.7%) by TS-CL. Failure to restore cSVA was associated with worse preoperative C2 pelvic tilt angle (CPT: 64.4° vs. 47.8°, P  = 0.01), worse postoperative C2 slope (35.0° vs. 23.8°, P  = 0.004), TS-CL (35.2° vs. 24.9°, P  = 0.01), CPT (47.9° vs. 28.2°, P  < 0.001), "+" Schwab modifiers ( P  = 0.007), revision surgery ( P  = 0.05), and failure to address the secondary, thoracolumbar driver of the deformity ( P  = 0.02). Failure to correct TS-CL was associated with worse preoperative cervical kyphosis (10.4° vs. –2.1°, P  = 0.03), CPT (52.6° vs. 39.1°, P  = 0.04), worse postoperative C2 slope (30.2° vs. 13.3°, P  < 0.001), cervical lordosis (–3.6° vs. –15.1°, P  = 0.01), and CPT (37.7° vs. 24.0°, P  < 0.001). Multivariate analysis revealed postoperative distal junctional kyphosis associated with suboptimal outcomes by cSVA (odds ratio 0.06, confidence interval 0.01–0.4, P  = 0.004) and TS-CL (odds ratio 0.15, confidence interval 0.02–0.97, P  = 0.05). Conclusion: Factors associated with failure to correct the cSVA included revision surgery, worse preoperative CPT, and concurrent thoracolumbar deformity. Failure to correct the TS-CL mismatch was associated with worse preoperative cervical kyphosis and CPT. Occurrence of early postoperative distal junctional kyphosis significantly affects postoperative radiographic outcomes. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text